Honeycomb-like mesoporous nitrogen-doped carbon supported Pt catalyst for methanol electrooxidation. (November 2015) - Zhang, Li-Mei; Wang, Zhen-Bo; Zhang, Jing-Jia; Sui, Xu-Lei; Zhao, Lei; Gu, Da-Ming
Abstract: A novel nitrogen-doped carbon material with honeycomb-like mesoporous structure was synthesized via carbonization of polyaniline under template and acted as support for the Pt catalyst. Pyrolysis temperature plays a significant role in enhancing electrochemical performance of Pt/mesoporous nitrogen-doped carbon (Pt/MNC) catalyst. Considering comprehensively electrocatalytic activity and stability for methanol electrooxidation, MNC-900 (MNC prepared at pyrolysis temperature of 900 °C) is an appropriate support for Pt catalyst. Moreover, the electrochemical performance of Pt/MNC-900 catalyst is significantly superior to that of Pt/mesoporous carbon (Pt/MC) catalyst. The enhancement is attributed to N species introduced to the support and optimal proportion of pyridinic N, pyrrolic N and graphitic N. When the contents of pyridinic N, pyrrolic N and graphitic N achieve optimal proportion, MNC support reveals not only intense anchoring effect of Pt nanoparticles but also enhanced electric conductivity, further improving electrocatalytic activity and stability of the catalyst.